La Innovacion Curricular Educativa y Sus Efectos En El Mejoramiento de la Calidad Ofertada En La Unidad Educativa Victoria Macias De Acuña Del Canton Milagro - Macias Arroyo Franklin (2015)
this research is a contribution to education and collecting daily shortcomings in the learning processes involved with teachers, students,parents and managers. based on the on-site investigation on the application of curriculum innovation implemented by the present national government, we check with teachers problems, hardships they face in exercising their work in each classroom.